Simulation of local area network (LAN) computer network using cisco packet tracer at SMP Negeri 1 Grabagan - Amran, Ali; Zuhria, Sinta Ainun; Ramadhani, M. David; Susmawati, Putri Rahayu; Diana, Siti Nur; Ulum, Luluk Bahrul; Aulita, Rida Nur; Firdaus, Firman Aditya; Latifah, Dede; Astutik, Astutik (Institute of Computer Science (IOCS), 2024)
Computer network, especially together with information technology, are now considered fundamental in all fields. A company’s information technology infrastructure is a strategic resource that must be handled effectively. Information technology infrastructure provides continuous processing and flow of information throughout the organization. A computer network that links machines is called a local area network over short distances among two or more places. To keep the network infrastructure functioning properly network security is very important. Cisco packet tracer is one of the tools used in simulations to setup network security. To build a computer network, procedures related to the network area required. Local Area Network (LAN) is an abbreviation off Local Area Network. LAN consist of several computers connected in a network. In this network, each computer can accsess data from other computers. Additionally, computers can access data from other computers. Apart from that, computers connected to LAN can also run hardware such as printers from other computers, chat with other computer ownerm or play games together. Network simulations on cisco system Local Area Network (LAN) computers using cisco packet treacer is a program for imulatinng network device, the program is used as a learning and training tool.